A meta-analysis evaluating indirectly GLP-1 receptor agonists and arrhythmias in patients with type 2 diabetes and myocardial infarction - Zhijie Liu; Ning Bian; Shaorong Wu; Yiming Fan; Hairui Li; Jian Yu; Jun Guo; Dongdong Chen (Frontiers in Cardiovascular Medicine, 2022)
AimsAt present, the effects of Glucagon-Like Peptide 1 Receptor agonists (GLP-1RAs) on arrhythmia in patients with type 2 diabetes mellitus (T2DM) and myocardial infarction (MI) are still unclear. Hence, this systematic review and meta-analysis aimed to investigate this association.Methods and resultsPubMed, Embase, Cochrane Library, and Web of Science were searched from inception to 30 April 2022. Randomized controlled trials (RCTs) that compared GLP-1RAs with placebo and met the critical criterion of a proportion of patients with T2DM and MI > 30% were included to verify our purpose indirectly. The outcomes of interest included atrial arrhythmias, ventricular arrhythmias, atrioventricular block (AVB), sinus arrhythmia, and cardiac arrest. Relative risk (RR) and 95% confidence intervals (CI) were pooled using a random-effects model. We included five RCTs with altogether 31,314 patients. In these trials, the highest proportion of patients with T2DM and MI was 82.6%, while the lowest was 30.7%. Compared to placebo, GLP-1RAs were associated with a lower risk of atrial arrhythmias (RR 0.81, 95% CI 0.70–0.95). There was no significant difference in the risk of ventricular arrhythmias (RR 1.26, 95% CI 0.87–1.80), AVB (RR 0.95, 95% CI 0.63–1.42), sinus arrhythmia (RR 0.62, 95% CI 0.26–1.49), and cardiac arrest (RR 0.97, 95% CI 0.52–1.83) between groups.ConclusionGLP-1RAs may be associated with reduced risk for atrial arrhythmias, which seems more significant for patients with T2DM combined with MI. More studies are needed to clarify the definitive anti-arrhythmic role of this drug.